PROFESSIONAL DEVELOPMENT OF HISTORY AND CIVIC EDUCATION TEACHERS IN UKRAINE: PROBLEMS AND PROSPECTS - Salata, Oksana (Continuing Professional Education: Theory and Practice, 2024)
The article examines the development of civic competence of history and civic education teachers in the system of in-service training as a necessary condition for the development of civil society in Ukraine. The purpose of the study is to analyze the system of in-service training of history and civic education teachers in postgraduate education and their perception of their professional development process, as well as to reveal the main aspects of motivation to improve their skills and develop the civic competence of history and civic education teachers. It is shown that anthropologism as a scientific concept that considers the individual as a subject of educational activity and social relations, recognizes a person as a complex system that develops itself according to internal and external laws, is of methodological importance for in-service training in the system of postgraduate education. In the course of the study, the methods of observation, oral communication and analysis were used. The problems and difficulties of cross-cutting civic education in the educational process and the subject area of each of the subjects taught in general secondary education institutions are shown. The study has shown that the vast majority of history and civic education teachers are eager to acquire new knowledge, are well aware that professional development can contribute to profound changes in teaching if it is based on classroom practice, is continuous and is carried out in collaboration with other teachers. The vast majority of teachers understand that when they learn and develop their own competencies, they transform their knowledge into practice for the benefit of their students’ development.